AB0669 Maintenance treatment with adalimumab in refractory uveitis due to behÇet's disease: optimised vs non-optimised group. (12th June 2018) - Martín-Varillas, J.L.; Calvo-Río, V.; Beltrán, E.; Sánchez, J.; Mesquida, M.; Adán, A.; Hernández, M.V.; Hernández, M.; Valls, E.; Martínez, L.; Sellas, A.; Cordero, M.; et al.
Abstract : Background: Uveitis is the most common ocular manifestation in Behçet's Disease (BD), which can cause irreversible blindness. 1–2 Objectives: To assess efficacy, safety and cost-effectiveness of adalimumab (ADA) therapy optimisation in a series of patients with uveitis due to BD. Methods: Multicenter study of 74 ADA-treated patients with BD uveitis refractory to conventional immunosuppressants. Following remission, optimisation was performed by increasing the ADA dosing interval. Comparison between optimised and non-optimised group was performed. Results: Ocular remission was achieved in 65 (86.6%) patients after a median ADA duration of 6 3–12 months. ADA was optimised in 23 cases. In the remaining 42 ADA was maintained at 40 mg/sc/2 weeks. No baseline differences were found at ADA onset between the optimised and non-optimised groups. Ocular outcomes were similar after a mean ±S.D. follow-up of 34.7±13.3 and 26±21.3 months in the both groups (table 1). Adverse effects were seen in non-optimised group (lymphoma, pneumonia, local reaction and bacteremia). Mean ADA treatment costs were lower in the optimised vs non-optimised group (6101.25 €/patient/year vs 12339.48). Conclusions: ADA optimisation in BD uveitis refractory to conventional therapy is effective, safe and cost-effective. References: [1] Calvo-Río V, Blanco R, Beltrán E, et al. Anti-TNF-alfa therapy in patients with refractory uveitis due to Behçet's disease: a 1-year- follow-up study of 124 patients. Rheumatol. 2014; 53(12):2223–31 [2] Santos-Gómez M, Calvo-Río V, Blanco R, et al. The effect of biologic therapy different from infliximab or adalimumab in patients with refractory uveitis due to Behçet's disease: results of a multicentre open-label study. Clin Exp Rheumatol. 2016; 34 (6Suppl 102):S34-S40 Disclosure of Interest: None declared